Input switched closed-loop single phase ĈUK AC to DC converter with improved power quality - Md. Shamsul Arifin; Nur Mohammad; Mohammad Ibrahim Khalil; Mohammad Jahangir Alam (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
A new closed loop AC to DC ĈUK converter is presented in this paper. The conventional ĈUK AC to DC converter has no feedback circuit. Thereby, the output voltage of the converter changes while changing the load. The proposed closed loop converter can regulate voltage with the variation of load over a wide range. Moreover, the power factor and Total Harmonic Distortion (THD) of the supply side current found quite satisfactory from this closed loop ĈUK converter. The converter operates in four steps with a different combination of voltage polarities and switching states. The feedback path consists of a voltage control loop and a current control loop. The closed loop ĈUK converter in this study is compared with the open loop version. Additionally, the comparison is made with the conventional converter of the same topology. The effectiveness in terms of power factor and THD of the proposed converter is verified using simulation results.